PENYULUHAN DAN PEMERIKSAAN HIPERPLASIA PROSTAT TERHADAP LANSIA PRIA di CIANGSANA dan NAGRA - Krismanuel, Hari; Tjhin, Purnamawati; Agil, Nadifa; Suparjo, Tjhang; Alvina, Alvina (Jurnal Pengabdian Masyarakat Trimedika, 2024)
Prostate hyperplasia is a condition in which there is hyperplasia of the stromal and epithelial cells of the prostate gland. This condition can be experienced by around 20% of men aged 41-50 years, 50% of men aged 51-60 years, up to more than 90% of men aged >80 years. As human life expectancy increases, the number of elderly people in society increases. This causes more and more elderly men to experience prostate hyperplasia. This condition is also experienced by people in the Ciangsana and Nagrak area. Meanwhile, the level of public knowledge regarding the symptoms and signs of prostate hyperplasia is still lacking. This situation causes a lack of public awareness about seeking treatment and increases the anxiety experienced by sufferers. The aim of this PKM is to increase public knowledge of the symptoms and signs of prostate hyperplasia and to screen for prostate hyperplasia among elderly men aged 60 years or more in the Ciangsana and Nagrak areas. This PKM method uses an education, preceded by a pre-test before education and a post-test after education. After that, a digital rectal examination is carried out to diagnose Prostate Hyperplasia. The data obtained consisted of pre-test and post-test results as well as data on Prostate Hyperplasia sufferers from counseling participants. The conclusion obtained in the form of Prostate Hyperplasia education increases the knowledge and level of awareness of counseling participants and the percentage of Prostate Hyperplasia sufferers from male elderly participants in Ciangsana and Nagrak is quite high (64.52%). The implication of this PKM is that people can detect early symptoms and signs of Prostate Hyperplasia and immediately go to a health facility.